COVID-19 Impact on Income and Expenditures Pattern of Household - Munish Gupta, Prof. S. N. Mahapatra (South Eastern European Journal of Public Health, 2025)
This paper provides a comprehensive analysis of studies conducted on the impact of COVID-19 in India, focusing on change in income level and consumption and expenditure pattern and overall economic stability. By study of various research papers, journals, articles we highlight the immediate and long term effect of COVID-19 on personal income, consumption, expenditure and saving etc. However COVID-19 affects all the sphere of economy as whole and exacerbated existing disparities, significantly affecting consumer behaviour, income, expenditure, employment, and livelihoods among rich and poor households, necessitating targeted economic policies and interventions. The media and entertainment industry has faced significant challenges, presenting emergent business opportunities and challenges. Studies have also explored the impact on energy consumption patterns, water security strategies, non-vegetarian diets, and shifts in consumer behaviour during crises. Additionally, the pandemic has highlighted the importance of comprehensive health and social support systems. Various studies provide insights into the impacts on agriculture, poultry industry, wholesale prices, trade volumes, employment dynamics, and food consumption patterns, offering valuable insights for recovery and resilience strategies. Our study shows the result that a significant decline in income affects the consumption behaviour and expenditure pattern of the most of the people. Declined income decrease the spending upon non-essential item as well increased spending upon essential items, healthcare, and hygiene foods. The study concludes with policy formation to recover economy and balanced the affected life of population.